2021
DOI: 10.1055/a-1381-7301
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative diagnostic accuracy of EUS needles in solid pancreatic masses: a network meta-analysis

Abstract: Background and study aims Endoscopic ultrasound (EUS)-guided tissue sampling is the standard of care for diagnosing solid pancreatic lesions. While many two-way comparisons between needle types have been made in randomized controlled trials (RCTs), it is unclear which size and type of needle offers the best probability of diagnosis. We therefore performed a network meta-analysis (NMA) to compare different sized and shaped needles to rank the diagnostic performance of each needle. Methods We searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 68 publications
1
9
1
Order By: Relevance
“…[ 26 ] Moreover, 90.72% of the tissue specimens acquired with the 25G ProCore needle were adequate for immunohistochemical staining, so that neoplastic diseases could be specifically diagnosed. Furthermore, in previous studies involving 22G needles, a lower diagnostic accuracy was often observed for lesions located in the head and uncinate or those with diameters <2 cm,[ 10 12 19 27 ] but this was not the case in the present study. According to the multivariate analysis, a mass measuring smaller than 2 cm was even significantly associated with a higher diagnostic sensitivity in the SS group.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…[ 26 ] Moreover, 90.72% of the tissue specimens acquired with the 25G ProCore needle were adequate for immunohistochemical staining, so that neoplastic diseases could be specifically diagnosed. Furthermore, in previous studies involving 22G needles, a lower diagnostic accuracy was often observed for lesions located in the head and uncinate or those with diameters <2 cm,[ 10 12 19 27 ] but this was not the case in the present study. According to the multivariate analysis, a mass measuring smaller than 2 cm was even significantly associated with a higher diagnostic sensitivity in the SS group.…”
Section: Discussioncontrasting
confidence: 83%
“…Compared to a 19G or 22G needle, the 25G needle has a smaller diameter and higher flexibility, which might lead to a higher technical success rate and wider applicability, especially in the head/uncinate of the pancreas. [ 19 ] However, the actual suction force applied at the 25G needle tip can be weakened as the needle diameter and syringe aspiration volume decreased. [ 20 ] Besides, so far, no prospective clinical trial has tested the efficacy of these three techniques for solid pancreatic lesions using a 25G ProCore needle in one trial.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Van Rietet al included 14 randomized controlled trials on cancerous and non-cancerous lesions and found that the EUS-FNB was superior to EUS-FNA (diagnostic accuracy 87% vs. 80%, p = 0.002) [ 8 ]. Finally, a network meta-analysis by deHan et al, including cancerous and non-cancerous lesions also showed that EUS-FNB was superior to EUS-FNA [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic accuracy is the primary outcome in most studies comparing the yield of different needle types. The diagnostic accuracy of FNA needles for pancreatic cancer is generally lower than for FNB needles [ 6 , 7 , 8 , 9 ]. The aim of this systematic review and meta-analysis was to compare the diagnostic yield of EUS-FNA cytology needles with that of the various EUS-FNB needles.…”
Section: Introductionmentioning
confidence: 99%
“…Peter Vilmann first performed EUS-TA for the cytologic diagnosis of a pancreatic lesion in 1991 [ 18 ].This technique has now become the standard method for tissue acquisition from pancreatic and peripancreatic lesions [ 14 , 19 ]. A recent network meta-analysis demonstrated better accuracy with 22-gauge FNB needles than conventional 22-gauge FNA needles [ 20 ], but it did not compare the performance between different types of FNB needles, namely, side-fenestrated needles, Franseen-tip needles, and Fork-tip needles. About this issue, another network meta-analysis in 2022 demonstrated the higher accuracy of Franseen-tip needles and Fork-tip needles than reverse-bevel needles and conventional FNA needles [ 21 , 22 ], especially in the absence of ROSE [ 3 ].…”
Section: Discussionmentioning
confidence: 99%